Multi-dimensional role of gangliosides in modulating cancer hallmarks and their prospects in targeted cancer therapy - Sarkar, Abhisek; Banerjee, Sounak; Biswas, Kaushik (Frontiers in Pharmacology, 2023)
Gangliosides are glycosphingolipids with prevalence in nervous tissue and their involvement in certain neuronal diseases has been widely known. Interestingly, many recent studies highlighted their importance in the development and progression of various cancers through orchestration of multiple attributes of tumorigenesis i.e. promoting migration, invasion, escaping the host immune system, and influencing other cancer hallmarks. Therefore, the multidimensional role of gangliosides in different cancers has established them as potential cancer targets. However, the tremendous structural complexity and functional heterogeneity are the major challenges in ganglioside research. Moreover, despite numerous immunotherapeutic attempts to target different gangliosides, it failed to yield consistent results in clinical trials owing to their poor immunogenicity, a broad range of cross-reactivity, severe side effects, lack of uniform expression as well as heterogeneity. The recent identification of selective O-acetylated ganglioside expression in cancer tissues, but not in normal tissues, has strengthened their potential as a better and specific target for treating cancer patients. It was further supported by reduced cross-reactivity and side effects in clinical trials, although poor immunogenicity remains a major concern. Therefore, in addition to characterization and identification of the biological importance of O-acetylated gangliosides, their specific and efficient targeting in cancer through engineered antibodies is an emerging area of glycobiology research. This review highlights the modulatory effect of select gangliosides on different hallmarks of cancer and presents the overall development of ganglioside targeted immunotherapies along with recent progress. Here, we have also discussed the potential for future modifications aimed towards improvement in ganglioside-based cancer therapies.